2021
DOI: 10.3390/su14010307
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and Cultural Sustainability: Views and Prospects from Cyclades, Greece

Abstract: The objective of this paper is to explore cultural tourism perceptions, practices, concerns and prospects among local residents, tourists and business representatives in the Cycladic Islands, specifically three sites (Andros, Syros and Santorini). The concept and framework of cultural sustainability are employed to analyze the variable interrelationships between culture and tourism in the development of cultural tourism and in overall local sustainability, from a bottom-up/destination perspective. The methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 41 publications
0
29
0
1
Order By: Relevance
“…However, if the demand side suffered, the supply side of Cyclades cultural tourism suffered even more, with businesses struggling to survive the crisis, on all fronts. Thus, according to our second research question findings, Greek tourism entrepreneurs expressed fatigue in having to assume the brunt of sustenance of the country's tourism sector without the State's help, called to operate in a 'hostile environment' (Terkenli & Georgoula, 2021). Although significant progress had been initiated and instigated in the years before the Greek socio-economic crisis (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) and the Covid-19 pandemic, in terms of more sustainable/ 'green', innovative/ creative, and technologically upgraded cultural development and cultural tourism development, this progress was put to hold by the pandemic, with unpredictable future prospects.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, if the demand side suffered, the supply side of Cyclades cultural tourism suffered even more, with businesses struggling to survive the crisis, on all fronts. Thus, according to our second research question findings, Greek tourism entrepreneurs expressed fatigue in having to assume the brunt of sustenance of the country's tourism sector without the State's help, called to operate in a 'hostile environment' (Terkenli & Georgoula, 2021). Although significant progress had been initiated and instigated in the years before the Greek socio-economic crisis (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) and the Covid-19 pandemic, in terms of more sustainable/ 'green', innovative/ creative, and technologically upgraded cultural development and cultural tourism development, this progress was put to hold by the pandemic, with unpredictable future prospects.…”
Section: Discussionmentioning
confidence: 91%
“…Indicatively, international tourist air arrivals in the Cycladic islands in 2019 reached 994,000 according to official statistical data (INSETE, 2020). Cultural tourism differs from island to island (Terkenli & Georgoula, 2021), and it does not represent a conscious tourism motive for most Cyclades visitors; however, broadly defined, culture remains the factor that underlies tourists' decision to visit these islands.…”
Section: 1mentioning
confidence: 99%
“…As previously mentioned, although culture can be used to promote a destination's identity, authors like du Cros (2009); Sou et al (2016) and Merrilees et al (2018) suggested to extend it as part of the social fabric of society, and Terkenli and Georgoula (2022) specifically proposed the use of communities to promote a brand for local tourism products. Given that many local residents have witnessed the establishment of Macao's entertainment facilities, and tried the entertainment products, particularly after the MSARG's subsidies to promote local tourism due to the Covid-19 pandemic, they may share their personal experience and opinions with the tourists.…”
Section: 2) Improved Entertainment Options With Culturementioning
confidence: 99%
“…The cultural dimension of sustainability, including the implications derived from tourism, creates a new level of analysis of the pillars of sustainability. Culture represents the most basic social feature of any destination, representing all forms of life of human beings (Terkenli and Georgoula, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…From the globalization context in which there are incentives to travel consumption, cultural heritage can be commodified by tourism, turning them into stories and emotional elements with economic appeal (Chang and Chuang, 2021). The heritage becomes a product that can be sold in a simplified way, without real characteristics of the community in which it is located, creating problems for cultural sustainability (Martins, 2021; Terkenli and Georgoula, 2021). It is common that societies associate heritage sites with the idea of preserved material goods of their ancestors for tourists' appreciation in an economic way, resembling the idea of Soini and Birkeland's economic viability (Martins, 2021; Terkenli and Georgoula, 2021).…”
Section: Introductionmentioning
confidence: 99%